The Effect of Squishy Ball Therapy on Anxiety Scores in Third Trimester Pregnant Mothers in the Work Area of Tamansari Community Health Center - Lisnia Desi Santika, Lisnia Desi Santika; Peni Cahyati, Peni Cahyati; Asep Riyana, Asep Riyana; Ridwan Kustiawan, Ridwan Kustiawan (Jurnal Medika Cendikia, 2025)
The third trimester of pregnancy is a period prone to increased anxiety due to physical and emotional changes, as well as concerns about the upcoming childbirth. If left unaddressed, anxiety may negatively affect both the mother and the fetus, leading to complications such as preterm labor or obstetric disorders. Based on this condition, this study aims to determine the effect of squishy ball therapy on anxiety scores among third-trimester pregnant women in the working area of Tamansari Public Health Center. The theoretical basis of this research includes the concepts of pregnancy, anxiety, maternal anxiety, squishy ball therapy, the benefits, use, and effects of squishy ball therapy. This study utilized a pre-experimental design with a one-group pretest-posttest approach, involving 19 respondents selected through purposive sampling. The instrument used was the Perinatal Anxiety Screening Scale (PASS) questionnaire. The paired t-test results showed a decrease in anxiety scores from a mean of 40.05 to 28.21 with a p-value of 0.000 (p < 0.05), indicating a significant effect. This decrease demonstrates that simple activities such as repeatedly squeezing a squishy ball can stimulate the parasympathetic nervous system, increase endorphin release, and produce a relaxing effect that helps reduce anxiety levels. This therapy is non-pharmacological, practical, easy to perform, and has no side effects, making it highly suitable for use as an independent nursing intervention. The conclusion of this study states that squishy ball therapy is effective in reducing anxiety in third-trimester pregnant women. It is recommended that this therapy be integrated into independent nursing practices in antenatal care services and be included as learning material in nursing education.